La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Fondation Musicaction, 2022)

Au-delà des "vagues" #moiaussi : Cinq ans de mobilisation féministe en musique au Québec (2017-2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2022)

Jumol-Julia Edéry’s Wedding in Early 20th Century Morocco - Cohen, Judith R. (Canadian Jewish Studies/Études juives canadiennes, 2022)

Alanis Obomsawin: Lifework - Hill, Richard William; Peleg, Hila; Haus der Kulturen der Welt (Prestel Publishing, 2022)
"One of today's most important documentary filmmakers, Alanis Obomsawin has dedicated her life's work to shining a light on the injustices experienced by Canada's Indigenous people. This retrospective monograph features an extensive interview with Obomsawin and includes stills and reflections on her entire career including her most recent series devoted to the rights of Indigenous children. Never shying away from controversy, Obomsawin's films have played a critical role in exposing ongoing systemic bias towards Indigenous populations-from fishing rights and education to health care and treaty violations. Obomsawin is also a graphic artist, and she incorporates her often dream-inspired etchings and prints into many of her films. This volume includes illuminating essays exploring Obomsawin's practice and mission as well as personal commentary from collaborators, archival materials, and photographs from the filmmaker's personal life and professional exploits. As Obomsawin closes in on her ninth decade of life-and fifth decade behind the camera-this beautifully illustrated record of her astounding body of work and tireless efforts on behalf of Indigenous peoples and culture is an inspiring celebration of the power of film to dramatically change the course of history"– Provided by publisher.

Une médiation de la musique au masculin ? Analyse des dispositifs numériques de médiation de la musique produits par les institutions musicales - Kirchberg, Irina (Digital Studies/Le champ numérique, 2022)
Dans le sillage de l’ouvrage dirigé par Octobre et Patureau (Octobre et Patureau 2018), cet article engage à une réflexion sur le traitement de la question du genre dans les dispositifs numériques de médiation produits par des organismes de diffusion et de production musicale. Les études en sociologie du travail artistique (Coulangeon et Ravet 2003 ; Buscatto 2007 ; Bousquet et al. 2018) ne cessent de montrer que l’ensemble des mondes de la musique, aussi bien classiques que jazz ou pop, est traversé par une double ségrégation genrée horizontale (répartition sexuée selon le type d’emploi) et verticale (moindre accès aux postes à responsabilités). On pourrait imaginer que les producteurs de dispositifs numériques de médiation de la musique, portant des valeurs de vivre-ensemble, d’inclusion sociale et d’agentivité (Perez-Roux et Montandon 2014 ; Carrel 2017), et conscients des effets normatifs et prescriptif des supports éducationnels (Octobre 2014), viennent questionner ces frontières. Le « dénombrement » et l’analyse de « cas » tirés du dépouillement systématique d’une centaine dispositifs numériques consultables en ligne et produits par des organismes de production et de diffusion musicale permettront de montrer que tel n’est pas le cas.

"[N]ou rasanble" : rassemblements hétérolingues et hétérogènes dans les chansons de Muzion - Leclerc, Catherine (Analyses, 2022)
Muzion a été parmi les tout premiers groupes de rap québécois à faire résonner une parole locale distinctive. Il le faisait dans un français mâtiné d’anglais et de créole haïtien, multipliant les registres et faisant des emprunts à encore d’autres langues. Cet article se penche sur les chansons du premier album du groupe, Mentalité moune morne, à partir de son hétérolinguisme et des questions d’appartenance que celui-ci soulève. Il examine la manière dont Muzion entrelace les langues, mais aussi les interpellations, défaisant l’association entre langue et identité. Le groupe s’adresse ainsi à la fois à une communauté immigrante locale (d’abord haïtienne, mais également pluriethnique et racisée) qu’il québécise, et à une communauté québécoise élargie qu’il pluralise. Le rap permet en outre à ses membres de faire entendre leurs voix individuelles distinctes, notamment grâce à des usages différenciés de la palette plurilingue du groupe. Ce faisant, ce sont les notions même d’appartenance et de communauté que Muzion se trouve à refaçonner, à l’encontre de toute forme d’homogénéisation, de figement ou de stéréotype.

Parcours professionnels de musiciennes migrantes : de la théorie à l'expérience. Note de terrain à propos du colloque Femmes musiciennes du monde tenu les 26 et 27 novembre 2021 au Centre des musiciens du monde - Marcoux-Gendron, Caroline; Champagne, Lysandre (La Revue musicale OICRM, 2022)

“Before I made fims, I was singing” - Obomsawin, Alanis; Gagnon, Monika Kin (Alanis Obomsawin: Lifework, 2022)

Les rappeuses québécoises sur le devant de la scène : autorité lyrique de la voix féminine chez Donzelle et MCM - Simard, Mathieu; Kirouac Massicotte, Isabelle (Analyses, 2022)

Stories I Might Regret Telling You: A Memoir - Wainwright, Martha (Hachette Books, 2022)
The singer-songwriter's heartfelt memoir about growing up in a bohemian musical family and her experiences with love, loss, motherhood, divorce, the music industry, and more. Born into music royalty, the daughter of folk legends Kate McGarrigle and Loudon Wainwright III and sister to the highly-acclaimed and genre-defying singer Rufus Wainwright, Martha grew up in a world filled with such incomparable folk legends as Leonard Cohen; Suzzy Roche, Anna McGarrigle, Richard and Linda Thompson, Pete Townshend, Donald Fegan, and Emmylou Harris. It was within this loud, boisterous, carny, musical milieu that Martha came of age, struggling to find her voice until she exploded on the scene with her 2005 debut critically acclaimed album, Martha Wainwright, containing the blistering hit, 'Bloody Mother F*cking Asshole,' which the Sunday Times called one of the best songs of that year. Her successful debut album and the ones that followed such as Come Home to Mama, I Know You're Married But I've Got Feelings Too, and Goodnight City came to define Martha's searing songwriting style and established her as a powerful voice to be reckoned with. In her memoir, Stories I Might Regret Telling You, Martha digs into the deep recesses of herself with the same emotional honesty that has come to define her music. She describes her tumultuous public-facing journey from awkward, earnest, and ultimately rebellious daughter, through her intense competition and ultimate alliance with her brother, Rufus, to the indescribable loss of their mother, Kate, and then, finally, discovering her voice as an artist. With candor and grace, Martha writes of becoming a mother herself and making peace with her past struggles with Kate and her former self, finally understanding and facing the challenge of being a female artist and a mother. Ultimately, Stories I Might Regret Telling You offers readers a thoughtful and deeply personal look into the extraordinary life of one of the most talented singer-songwriters in music today.

L’avenir. Les changements que les personnes répondantes souhaitent voir concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

L’état des choses. Le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Le suivi. Dénonciation, soutien et qui cause le préjudice? Concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision. - Aftermetoo (2021)
Keywords: Pas de lien web

Les dommages. Les répercussions sur les personnes survivantes du harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Principaux constats. Résultats de la toute première enquête sur le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Sur le terrain. La parole aux personnes survivantes. Suggestions écrites concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Gender and Extreme Metal: Understanding Gender Relations in the Montreal Extreme Metal Scene With Schippers' Gender Framework - Beauchamp, Caroline (Université Concordia, 2021)
Extreme metal is a masculine space, yet more and more women join in. They face a contradiction: as women, they are expected to adopt feminine behaviours; however, they are part of a subculture that valorizes warrior masculinity. I sought to understand the gender expectations of the Montreal extreme metal scene and interpret the contradictions encountered by women in this scene with the help of Schippers’ (2007) theoretical framework on gender. To do so, I conducted 16 individual interviews with women and men who take part in the scene. This research fills a gap in the literature on gender that derives from Connell and Schippers’ writings and addresses issues that the field of metal studies has brushed over. I found that metal men are the “default” participants in the scene. They are expected to be fine music connoisseurs and even become musicians. In contrast, women’s presence is heterosexualized and attributed to a romantic or sexual interest in metal men. Women are suspected of being “poseuses” or groupies with no real interest in the music until proven otherwise. To become legitimate participants, they have to overcome those expectations and prove that they are worthy of being viewed through the prism of masculinity rather than femininity. They do so by proving their exceptionality through manhood acts and distancing themselves from other women. Despite their gender transgressions, women’s presence does not fundamentally question gender relations but reaffirms the overall primacy of masculinity over femininity.

Myriam Boucher + Followup - Boucher, Myriam (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)
The caesura in musical production caused by recent global lockdowns has made contemporary music’s crisis of societal relevancy more apparent than ever. Bringing together interviews with music curators, musicians, activist networks and institutional leaders, this book details existing practices and approaches, showing that change is possible but only if the recent wave of interest in curatorial practices, diversity and divestment from a white, European bourgeois aesthetic are taken seriously by the musical establishment. This expanded second edition of Taking the Temperature adds a new preface, five new interviews, as well as followups with previous interviewees. Radiating out from the Ultima Festival and Oslo, ..

Les îles (2011) d’Isabelle Panneton et l’héritage de Philippe Boesmans : généalogie d’une démarche compositionnelle - Brasset, Marie-Pierre (Circuit : musiques contemporaines, 2021)
Dans les années 1980, après ses études auprès de Gilles Tremblay, Isabelle Panneton fait la rencontre de Philippe Boesmans lors d’un passage du compositeur belge à Montréal. Impressionnée par sa musique, elle se rendra en Belgique pour y suivre des leçons de composition avec lui de 1984 à 1987. Cette période sera déterminante pour la compositrice, ouvrant toute grande la porte à l’émergence de sa personnalité musicale. Ce texte retrace les moments forts du passage d’Isabelle Panneton chez le compositeur belge et met en lumière les liens qui les unissent, en guise de prélude à l’analyse de son trio Les îles pour violon, violoncelle et piano.
Publisher: Circuit, musiques contemporaines
Keywords: Belgique; Belgium; Isabelle Panneton; Philippe Boesmans; chamber music; développement motivique; motivic development; musique de chambre

Do We Really Want to Keep the Gate Threshold That High? - Brooks, Grace; Pras, Amandine; Elafros, Athena; Lockett, Monica (Journal of the Audio Engineering Society, 2021)
Drawing upon the survey instruments of Lewis and Neville [1], Nadal [2], and Yang and Carroll [3], we conducted an online survey that captured experiences of discrimination and microaggressions reported by 387 recording engineers, producers, and studio assistants living in 46 different countries. Our statistical analyses reveal highly significant and systemic gender inequalities within the field, e.g., cisgender women experience many more sexually inappropriate comments (p < e-14, large effect size) and unwanted comments about their physical appearance (p < e-12, large effect size) than cisgender men, and they are much more likely to face challenges to their authority (p < e-13, large effect size) and expertise (p < e-10, large effect size). A comparison of our results with a study about women’s experiences of microaggressions within STEM academia [3] indicates that the recording studio workplace scores 33% worse on the silencing and marginalization of women, 33% worse on gender-related workplace microaggressions, and 24% worse on sexual objectification. These findings call for serious reflection on the part of the community to progress from awareness to collective action that will unlock the control room for women and other historically and systemically marginalized groups of studio professionals.

Lise Vachon and “Octobre au mois de mai”: Relistening to the Québécois Revolution - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

Marie-Claire Séguin: Feminism and Settler Colonialism in “Mater Maria” - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

"If you see me walking alone on the road": Sephardic Songs of Exile, Expulsion, Memory – and Return - Cohen, Judith R. (Armenian and Jewish Experience between Expulsion and Destruction, 2021)

David Denada - Farnsworth, Brandon (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Barbara Scales - Farnsworth, Brandon; Massera, Vanessa (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Étude patrimoniale sur le katajjaniq - Gadoua, Marie-Pierre (Publications Nunavik, 2021)
Ce livre présente une résumé exhaustif de l’étude effectuée sur le katajjaniq, suite à la désignation de cette pratique à titre de premier élément du patrimoine immatériel québécois.

Interroger l'expérience d'un chœur féministe : le cas du Chœur Maha - Harrison-Boisvert, Catherine (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Black Women Dancers, Jazz Culture, and “Show Biz”: Recentering Afro-Culture and Reclaiming Dancing Black Bodies in Montréal, 1920s–1950s - Jabouin, Emilie (Canadian Journal of History, 2021)
The documentary Show Girls, directed by Meilan Lam, makes an unprecedented contribution to the history of jazz and Black women jazz dancers in Montréal, Quebec, and to the conversation of jazz in Canada. Show Girls offers a glimpse into the lives of three Black women dancers of the 1920s–1950s. This essay asks what the lives of Black women dancers were like and how they navigated their career paths in terms of social and economic opportunities and barriers. I seek to better understand three points: (1) the gap in the study of jazz that generally excludes and/or separates dance and singing from the music; (2) the use of dance as a way to commercialize, sell, and give visual and conceptual meaning to jazz; (3) the importance of the Black body and the role of what I would define as “Afro- culture” in producing the ingenious and creative genre of jazz. My study suggests there is a dominant narrative of jazz, at least in academic literature, that celebrates one dimension of jazz as it was advertised in show business, and that bringing in additional components of jazz provides a counternarrative, but also a restorative, whole and more authentic story of jazz and its origins. More specifically, by re- exploring jazz as a whole culture that relies on music, song, and dance, this essay explores three major ideas. First, Black women dancers played a significant role in the success of jazz shows. Second, they articulated stories of self, freedom, and the identity of the New Negro through jazz culture and dance. Third, Black women’s bodies and art were later crystallized into images that further served to sell jazz as a product of show business.

Dick Montgomery et la personnification féminine afrodescendante en Amérique du Nord, 1935-1960 - Jacques, Raphaël (Histoire Engagée, 2021)

Terri Hron (Canadian New Music Network) - Jakobsson, Anna (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Black Gold: A Black Feminist Art History of 1920s Montréal - Joachim, Joana (Canadian Journal of History, 2021)
The 1920s have been touted as the golden era of jazz and Black history in Montréal. Similarly, the decade is well known for the Harlem Renaissance, a key moment in African American art history. Yet this period in Black Canadian art histories remains largely unknown. As a first step toward shedding some light on this period in Black Canadian art history, I propose to use what I term a Black feminist art-historical (bfah) praxis to discuss some visual art practices undoubtedly active alongside well-known jazz musicians and cultural producers in 1920s Montréal. This paper presents an overview of critical race art history and feminist art history, as well as Black feminist approaches to visual representation, to outline what might be considered four tenets of bfah praxis. Applying these tenets, I propose that a new art history may emerge from well-known art objects and practices as well as lesser-known ones. I posit that through a deliberately bfah approach, new meanings emerge and the voices of Black women, even when obstructed by mainstream white narratives, may begin to stand out and shed light upon a variety of histories. This praxis aims to underline the subtext lurking at the edges of these images and to make intangible presences visible in the archive and in art history. I propose bfah as a strategy for more nuanced discussion of the work of Black Canadian artists and histories that have by and large been left out of official records.
Publisher: University of Toronto Press

Nueva vida : Mener la danse avec un trouble de santé mentale - K, Florence (2021)
« Un trouble de santé mentale impose souvent le travail d'une vie, soit un profond apprentissage de soi, de sa maladie et de la maîtrise de celle-ci. Pour arriver un jour à valser avec son état et à mener la danse. » Nueva vida, c'est le récit d'un cheminement vers une nouvelle vie. C'est la preuve que, comme les chats, on peut retomber sur ses pattes neuf fois, sinon plus. Après la parution de Buena vida, alors que tout devrait bien aller, Florence K sent encore le trou noir qui la guette. Puis un psychiatre pose enfin un diagnostic sur le précipice au bord duquel elle marche depuis plusieurs années : celui de la bipolarité de type II. À partir de ce moment, avec un suivi et un traitement adapté, elle a pu atteindre un équilibre durable. Dans ce récit touchant, elle se livre avec transparence, pour briser les tabous et la solitude, plaider pour un meilleur accès aux soins et apporter de l'espoir à tous ceux qui connaissent les aléas vertigineux d'un trouble de santé mentale.

Énonciation, sexualités et genre en musique chez Philémon Cimon, Pierre Lapointe et Ariane Moffatt - Konaté, Khady (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Dans ce texte est proposée une « lecture du genre » (Boisclair 2002) des oeuvres de Philémon Cimon (L’été, Les femmes comme des montagnes), Pierre Lapointe (Pierre Lapointe, Sentiments humains) et Ariane Moffatt (Aquanaute, Le coeur dans la tête, Tous les sens). L’étude des chansons contenues sur ces albums prend pour point de départ une interrogation des subjectivités genrées de ces trois artistes, entre personne réelle et persona, et montre que ces dernières façonnent leurs compositions. La sollicitation du concept de sexe/genre ouvre dès lors la porte à l’exploration des représentations des identités sexuelles et de genre dans ces chansons, où les identités des artistes se trouvent mises en abîme. En s’intéressant à l’énonciation et au discours (en particulier, au discours amoureux) contenu dans le texte des chansons sélectionnées, il est possible de rendre compte de la reproduction des injonctions à l’hétérosexualité et des poncifs qui cloisonnent le genre, ainsi que des glissements et brouillages qui autorisent des resignifications du genre. Ainsi, chez Cimon, on observe la reconduite du point de vue masculin où la valeur du féminin réside dans sa capacité à émerveiller le sujet et à susciter son désir. À l’opposé, les textes de Lapointe et Moffatt dépeignent des personnages et des récits queer, bien que leur identité queer n’ait pas été revendiquée à l’heure de la parution de leurs oeuvres.

Une chanteuse épanouie : Renée Claude (1939-2020) - Laberge, Yves (Cap-aux-Diamants : la revue d'histoire du Québec, 2021)
Un article de la revue Cap-aux-Diamants, diffusée par la plateforme Érudit.
Publisher: Les Éditions Cap-aux-Diamants inc.

Chronologie de plus de cent ans de présence féminine dans la création d'œuvres musicales au Québec : un premier survol - Lefebvre, Marie-Thérèse (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Lynda Lemay. Il était une fois mes chansons - Lemay, Lynda; Vignol, Baptiste (Éditions Gründ, 2021)

Genre, rap et enjeux de la visibilité dans l'espace public des rappeuses à Montréal : de la gestion de l'apparence physique pour être reconnue en tant qu'artiste - Lesacher, Claire (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Avant-propos. Björk, Montréal et le Nunavut - McKinley, Maxime (Circuit : musiques contemporaines, 2021)
An article from Circuit, on Érudit.
Publisher: Circuit, musiques contemporaines

Mary Travers Bolduc ou Madame Édouard Bolduc, pionnière de la chanson populaire au Québec - Melançon, Johanne (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Longtemps dénigrée par une certaine élite et plus ou moins ignorée des ouvrages sur la chanson, Mary Travers Bolduc (1894-1941) est aujourd’hui considérée comme étant la première autrice-compositrice-interprète, ainsi que la toute première vedette de la chanson populaire québécoise. À une époque où les femmes bénéficient de peu ou pas d’autonomie, sa carrière semble à la fois une anomalie et un exploit. Cependant, l’image de la femme indépendante qui gère sa carrière et organise ses tournées apparaît en contradiction avec les chansons où elle reste fidèle aux valeurs traditionnelles de sa génération et de son public quant au rôle de la femme dans la société. Réécouter les chansons de Mme Bolduc et parcourir les archives permettent de mieux comprendre qui était celle que l’on surnommait « La Bolduc », — à la fois femme, épouse et mère, ainsi qu’artiste autodidacte et « reine de la chanson comique », à mi-chemin entre le folklore et la chanson populaire —, et aident à la compréhension de ce pourquoi sa réception critique a été aussi longtemps mitigée. On peut également mieux mesurer la valeur de son oeuvre en lien avec la société dans laquelle elle a évolué, ainsi qu’émettre le constat que la condescendance de certains à son égard au cours de sa carrière, tout comme le silence qui a suivi son décès, relèvent de préjugés ; non pas parce qu’elle était une femme, mais à cause de la classe sociale à laquelle elle appartenait et dont elle a été le miroir. Ce n’était pas tant le propos de ses chansons qui dérangeait mais bien son niveau langue, le ton parfois grivois et le style de sa musique, ce qui a pourtant garanti son succès auprès des spectateurs. Sa réhabilitation au cours des années 1960, dans le contexte d’une revalorisation du folklore et de l’âge d’or de la chanson joualisante, s’explique par l’évolution de l’horizon d’attente et du goût du public.

Dream visions: The Art of Alanis Obomsawin - Obomsawin, Alanis (Perceval Press, 2021)

The Double Bind That Is Not a Bond: Cohen and Women - Pally, Marcia (From This Broken Hill I Sing to You: God, Sex, and Politics in the Work of Leonard Cohen, 2021)
Leonard Cohen's troubled relationship with God is here mapped onto his troubled relationships with sex and politics. Analysing Covenantal theology and its place in Cohen's work, this book is the first to trace a consistent theology across sixty years of Cohen's writing, drawing on his Jewish heritage and its expression in his lyrics and poems.Cohen's commitment to covenant, and his anger at this God who made us so prone to failing it, undergird the faith, frustration, and sardonic taunting of Cohen's work. Both his faith and ire are traced through: · Cohen's unorthodox use of Jewish and Christian imagery · His writings about women, politics, and the Holocaust · His final theology, You Want It Darker, released three weeks before his death.
Keywords: Music / General; Religion / Judaism / Theology; Religion / Theology

Alys Robi a été formidable. Nouveau regard sur une figure d'avant-garde - Ringuet, Chantal (Québec Amérique, 2021)
Flamboyante et indépendante, Alys Robi a marqué le Québec en étant sa première star internationale puis en voyant sa carrière s’interrompre brutalement, à vingt-cinq ans à peine, lorsqu’elle est internée contre son gré. Mais au-delà de ces deux grands axes à partir desquels on la raconte toujours, qui était-elle ? Pourquoi a-t-elle été internée ? Pourquoi, surtout, a-t-on oublié à quel point elle a été formidable ?Chantal Ringuet a plongé dans les archives de cette femme qui était sa grand-tante afin d’en brosser enfin un portrait exhaustif et de réhabiliter la mémoire d’une artiste exceptionnelle. Dans cette émouvante biographie qui flirte avec l’essai littéraire, elle nous entraîne dans l’envers du décor, sur les traces de cette diva qui a été tour à tour reine de la chanson, féministe avant l’heure, traductrice littéraire, porte-parole pour la santé mentale, incarnation du kitsch et égérie de la communauté gaie. Une femme qui, malgré les épreuves inouïes qu’elle a affrontées, a poursuivi son chemin la tête haute.

Les femmes et la chanson au Québec : quels cadrages ? pour quelles histoires ? - Savoie, Chantal (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Black Media Reporting on Theater, Dance, and Jazz Clubs in Canada: From Shuffle along to Rockhead’s Paradise - Thompson, Cheryl; Jabouin, Emilie (Journal of Communication Inquiry, 2021)
Canada has a history of de facto Jim Crow (1911–1954). It also has a historical Black press that is intimately connected to Black America through transnational conversations, and diasporic migration. This article argues that Canada’s Black newspapers played a pivotal role in promoting Black performance during a time when they were scarcely covered in the dominant media. Drawing on news coverage from the 1920s through 1950s of black dance, musicals, and jazz clubs this article examines three case studies: Shuffle Along (1921–1924), the first all- Black Broadway musical to appear at Toronto’s Royal Alexandra Theater, Alberta-born dancer Len Gibson (1926–2008), who revolutionized modern dance in Canada in the 1940s and 1950s, and the Montreal jazz club Rockhead’s Paradise (1928–1980), a pivotal site in the city’s Little Burgundy, a Black neighborhood that thrived in the 1930s through 1950s. The authors argue that when Black people were excluded from and/or derogatorily portrayed in the dominant media, Canada’s Black press celebrated collective achievement by authenticating Black performance. By incorporating Canada’s Black Press into conversations about Jim Crow and performance, we gain a deeper understanding of Black creative output and resistance during the period.
Publisher: SAGE Publications Inc

Situer les femmes dans l'Electronic dance music culture (EDMC) à Montréal, entre 1950 et 1955 : premier survol - Van Vliet, Kiersten (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Quadruple défi pour les artistes femmes, immigrantes et allophones : Le cas du premier Sarau das Minas Montréal - Vasconcellos de Carvalho, Dalila (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Fracturing Patriarchal Objectivity through Electro-Pop: Purity Ring and the vicissitudes of sight - Watkinson, Philip (Performance Research, 2021)
This article examines the deviated modes of seeing in the work of Canadian electro-pop band Purity Ring. Bringing their recent music into conversation with the theory of Tim Ingold and Eugenie Brinkema, I suggest that Megan James and Corin Roddick perform seeing as a granular, augmented act that continually shapes the boundaries between our bodies and the world around us. Particular attention is paid to James and Roddick’s creative engagement with optical touch and the formal capability of music to engage affectively with the act of seeing.By integrating musical examples, Tallulah Fontaine’s artwork for the band and the poetry of Kiran Millwood Hargrave, this article offers an expanded reading experience that spans the textual, the aural and the visual. I argue that the political crux of Purity Ring’s performance of perception lies in them moving beyond a reactionary response to patriarchal objectivity and towards a creative refiguration of perception as a form of subjectivation. The eyes that Purity Ring instantiate do not passively observe the world; they change it, both consoled and engulfed by the vicissitudes of perception.

« Changer le monde un hit à la fois » ? Programmation et diversité à CKOI-FM - Watson, Jada (Les Cahiers de la Société québécoise de recherche en musique, 2021)
En mars 2019, Stéphanie Vallet a publié un article dans La Presse portant sur la sous-représentativité des artistes féminines dans le palmarès Billboard « Canadian Hot 100 ». Les résultats de son étude démontrent une forte décroissance de la présence des femmes dans l’industrie musicale canadienne — un écosystème dans lequel les ondes radio continuent de jouer un rôle important quant à la découvrabilité et à la professionalisation des artistes. Cependant, au-delà des questions de genre abordées par Vallet, les enjeux liés à la représentativité des artistes issu·es de la diversité ethnoculturelle et linguistique à la radio doivent également être soulevés. Les théories de « social remembering » (Misztal 2003 ; Strong 2011) offrent un cadre critique pour se pencher sur les « Big Data » compilées par des industries où les femmes et les artistes racisé·es semblent systématiquement désavantagé·es. Dans le but d’entamer le portrait de la représentativité sur les ondes de la radio commerciale au Québec, cet article aborde la représentativité des artistes minorisé·es sur les ondes de CKOI-FM (96.9) de Montréal. CKOI-FM a été choisie non seulement parce qu’il s’agit d’une station francophone « top 40 » (diffusant tous les genres musicaux), mais aussi parce qu’entre 2015 et 2017 elle utilisait le slogan « Changeons le monde un hit à la fois » (Girard 2017) — un message à fortes résonances avec les slogans militants visant la justice sociale. Ce projet offre donc l’occasion d’investiguer la validité des déclarations faites par une radio qui se vante de « changer le monde ». En adoptant une approche féministe intersectionnelle à l’analyse des données appelée « data feminism » (d’après D’Ignazio et Klein 2020), cette étude évaluera les différents taux de représentativité à CKOI-FM parmi les 100 chansons les plus jouées chaque année entre 2010 et 2020 afin de considérer le rôle que jouent les ondes radio dans la formation de la culture musicale populaire au Québec et, par extension, de la mémoire sociale.

Sounding the Arctic in Chantal Bilodeau’s Climate Change Plays - Balestrini, Nassim W. (Nordic Theatre Studies, 2020)
Quebec-born playwright Chantal Bilodeau has been responding to the challenges of dramatizing anthropogenic climate change by developing an eight-part Arctic Cycle, each play of which is set in one of the nations that claims Arctic territory. Sila (2014) immerses audiences into a complex network of humans, animals, and mythical beings crisscrossing the Canadian Arctic. These movements circle around the Inuit concept of sila, which is the life-giving force of breath and voice. Thus, the sonic world of Sila focuses on voices speaking words, on performance poetry, and on the sounds of breath and wind. Bilodeau’ s second Arctic Cycle play, Forward (2016), addresses the long-term impact of Fridtjof Nansen’s polar exploration of the 1890s on Norway’s economy and society. In terms of sound, Forward features multiple musical performances rangingfrom traditional songs to European opera arias and Lieder to contemporary Norwegian electro-pop. The sonic features of both plays stress interdependence across time, space, as well as (non-)human, earthly, and metaphysical realms. Sila and Forward address climate change in a non-universalizing manner which promotes a heterarchical (rather than hierarchical) aesthetic fit for a growing awareness of planetary relationality.
Keywords: Theory and practice

Gender and Embodiment in the Contemporary Montreal Swing Dance Community - Batty, Megan (Université McGill, 2020)
"This thesis explores embodiment and gender within the contemporary Montreal swing dance community. Drawing on scholarship in musicology, dance studies, jazz studies, and gender studies, I investigate the relationship between dancers and musicians/DJs. I explore the many facets of this choreomusical conversation and trace this dialogic and collaborative relationship on the social dance floor. The contemporary community is a product of the swing revival and navigating issues of authenticity thus becomes an important consideration for dancers, musicians, and DJs alike. One product of this revival is the set of heteronormative values that underpin the contemporary community. I investigate to what extent these values are reified, challenged, or altogether subverted by participants through musical and choreomusical choices. To this end I conducted interviews with six informants, each of whom has experience as both a dancer and musician and/or DJ. Their privileged position arising from their dual experience affords them insight on the ways in which dancers and musicians/DJs function within the community. This thesis builds on existing scholarship by situating the voices of individuals with choreomusical experience in dialogue with existing scholarship, and ultimately revalues the importance of both embodied knowledge and gender within the swing community"– Author's abstract

Louise Campbell. Une médiatrice dans l’être - Bertomeu, Fanny (Revue musicale OICRM, 2020)
Formed as a musician and a clarinetist, Louise Campbell is now a music mediator. Based in Montreal, she practices her profession through several structures and for a wide variety of audiences (schoolchildren, professionals, people with disabilities ...) all around Canada, but mainly in Quebec. In this interview, Louise Campbell recounts her experience as a mediator, her (non)-formation in this profession, as well as many aspects in her practice. With the musical object and the creation at the heart of her workshops, Louise Campbell always seeks to establish a “horizontal” exchange relationship with each person she meets.
Publisher: Observatoire interdisciplinaire de création et recherche en musique (OICRM)
Keywords: Louise Campbell; creation; création; music mediation; médiation de la musique; partage; relation; relationship; sharing

“Maple Leaf Rag” in Maple Leaf Country: Impressing Jazz upon Vera Guilaroff - Blais-Tremblay, Vanessa (Women and Music: A Journal of Gender and Culture, 2020)
Publisher: University of Nebraska Press

Pauline Julien, intime et politique (2018) - Carlos, Jean-Philippe (Bulletin d'histoire politique, 2020)

Bïa Krieger versionista: Três cançoes de Chico Buarque em francês [Bïa Krieger, versionista. Trois chansons de Chico Buarque en français] - Cassiano, Raissa Conde (Université de São Paulo, 2020)

TAGS de Joane Hétu et TanGRAM de Danielle Palardy Roger : signatures plurielles et figure continue - Dall’Ara-Majek, Ana (Circuit : musiques contemporaines, 2020)
TAGS by Joane Hétu and TanGRAM by Danielle Palardy Roger are two written works that showcase graphic scores in improvised music. TAGS creates an encounter between Ensemble SuperMusique, the saxophone quartet Quasar, and the Bozzini Quartet. The musicians make “sound graffiti” on an imaginary wall represented by a sequence of timed sections on a descriptive score where the composer uses different instrumental combinations. Using an aesthetic of articulated gestures, the work is made through these multiple signatures. TanGRAM brings together twenty instrumentalists from Ensemble SuperMusique. The game of Tangram is represented in the form of a graphic score where each piece has specific musical properties to be interpreted by the musicians. Rich in combinatorial and symmetrical games, the work presents Orion: a continuous figure, a slowly moving flow where each musician seeks their own way in a global sound.
Publisher: Circuit, musiques contemporaines
Keywords: Analyse musicale; Danielle Palardy Roger; Joane Hétu; Musical analysis; graphic score; improvised music; musique improvisée; partition graphique

Blondie B, rappeuse des premières heures au Québec - Desfossés, Félix B. (Les racines du hip-hop au Québec. Tome 1, 2020)

Wavy Wanda et Baby Blue, pionnières du rap à Montréal - Desfossés, Félix B. (Les racines du hip-hop au Québec. Tome 1, 2020)

Mouffe. Au cœur du showbiz - Dumas, Carmel; Monfette, Claudine (Éditions La Presse, 2020)
La parolière d’Ordinaire et du Mur du son, c’est elle. La muse du jeune Charlebois, c’est encore elle. La metteure en scène de spectacles mythiques (Magie rose, J’ai vu le loup, le renard, le lion) et d’innombrables galas, c’est toujours elle. « Elle », c’est Mouffe, figure légendaire du Québec en marche, née Claudine Monfette, alouette ! Diplômée de l’École nationale de théâtre, interprète de chansons en duo et de rôles d’ingénue, éternelle tête chercheuse, semeuse de bonnes idées et mentore de la relève, elle a contribué à faire de notre milieu artistique ce qu’il est. Journaux personnels de Mouffe, entrevues avec celle-ci mais aussi avec sa famille, ses amis, ses collègues : Carmel Dumas a remonté pendant plus de dix ans le fil de cette vie palpitante et trace ici le portrait d’une femme omniprésente et effacée, fantaisiste et sage. Une vieille âme enveloppée de candeur, extraordinaire survivante.
Keywords: Biography & Autobiography / Artists; Architects; Photographers

Sacred Song Sisters: Choral and Solo Vocal Church Music by Women Composers for the Lenten Revised Common Lectionary - Elliott, Lisa A. (Université du Nevada, 2020)
This document explores sacred music by women composers for the Revised Common Lectionary (RCL) of the Catholic and Christian churches. The study researches exclusively choral and vocal solo music by women composers for the church season of Lent. Other primary limitations include music in English, and music from the nineteenth century to the present. The main question answered in this document is: what sacred music has been published by women composers that may be programmed in church services? This question is answered in the included appendices. These appendices list the music by women composers appropriate for the specific RCL readings for each Sunday of Lent, as well as the holidays of Ash Wednesday, Maundy Thursday, and Good Friday. There are also appendices of choral and solo vocal pieces that are generally appropriate for the Lenten season. Every attempt was made to be as thorough as possible in identifying this music, with the understanding that no one compilation of this kind can ever be complete. Additionally, selected works by six composers are explored in this document: Emma Lou Diemer (b. 1927), Arletta O’Hearn (b. ca 1928), Jane M. Marshall (1924 – 2019), Rebecca Clarke (1886 – 1979), Violet Archer (1913 – 2000), and Undine Smith Moore (1904 – 1989). These composers are representative of the variety of styles, diversity, history, and levels of musical complexity within this body of music.
ISBN: 9798662554733
Keywords: Choir; Christ; Female; Service; Sing; Worship

Renée Claude. Donne-moi le temps - Girard, Mario (Éditions La Presse, 2020)
À l’aube des années 1960, Renée Claude fait ses débuts de chanteuse en interprétant Ferré, Béart et Brassens, mais aussi, et surtout, les siens (Ferland, Léveillée, Vigneault, DesRochers, Lelièvre). Sa rencontre avec l’auteur-compositeur Stéphane Venne, puis son association avec le parolier Luc Plamondon marqueront un point tournant dans sa carrière. Pendant plus d’une décennie, Renée Claude enchaînera les succès. « C’est notre fête aujourd’hui », « Le début d’un temps d’un nouveau », « Le tour de la terre », « Viens faire un tour », « Tu trouveras la paix », « Un gars comme toi », « Ce soir je fais l’amour avec toi » ... Au début des années 1980, alors que d’autres chanteuses de sa génération rendent les armes, Renée Claude connaît une incroyable renaissance avec un cycle d’hommages à Clémence DesRochers, Georges Brassens et Léo Ferré. Offerts aux quatre coins du monde pendant plus de 30 ans, ces spectacles confirmeront son grand talent d’interprète. Grâce à des dizaines d’entretiens, le journaliste Mario Girard retrace le fascinant parcours de plus de 50 ans de cette artiste incomparable. À travers son histoire, il raconte aussi celle du Québec qui a émergé de la Grande Noirceur pour se tailler une identité à sa mesure. Et on peut affirmer que Renée Claude y a largement contribué.
Keywords: Biography & Autobiography / Entertainment & Performing Arts; Biography & Autobiography / General; Biography & Autobiography / Music

Jocelyne Binet's Cycle de Mélodies: Unearthing a Forgotten Song Cycle - Hoch, Matthew (Journal of Singing, 2020)
Montreal composer Jocelyne Binet's "Cycle de Melodies sur des Poemes de Paul Eluard" was programmed in 1955 by the French baritone Gerard Souzay in a performance that was most likely the world premiere. Unfortunately, Binet's song cycle never was published, and the work soon was forgotten. In the fall of 2016, the author discovered Bineet's original handwritten manuscript pages in holdings of Bibliotheque et Archives Nationales du Quebec and began the process of reconstructing the score. This article discusses the editorial journal undertaken when resurrecting Binet's forgotten song cycle, which was subsequently published in 2018 by Classical Vocal Reprints.
Keywords: Archives & records; Education; French language; Manuscripts; Music; Musical performances; Online data bases; Piano; Spelling; Vocal music

(Re)Presenting Indigenous Activism in the Nation's Capital: Signifying Resistance across Time and Place through Music in Alanis Obomsawin's Trick or Treaty? (2014) - Hoefnagels, Anna (Contemporary Musical Expressions in Canada, 2020)

Music, Geography and the Greatest Rewards: A Geohistorical Analysis on the Prestigious Awards of Céline Dion - Iconic Artist - Jucu, Ioan-Sebastian (Review of Historical Geography and Toponomastics, 2020)
In the present academic research connecting geography and music,a real gap remains in the study of different issues associated with both music and geography and, particularly, to the recent music geographies. This paper advances a new geographical approach in music geography highlighting the relevance of time and space in music, in the artist‟s outstanding contribution to music and in their recognition from the local to the global. Particularly the study is focused on one of the most emblematic music artists of the world, analyzing through a spatio-temporal investigation the prestigious awards achieved by the singer Celine Dion, since this singer remains both a real music legend and an iconic artist gaining multiple awards and thoroughly appreciated and admired for her outstanding contribution to music and global popular culture. The research bases on such specific methods as internet research, visual methodologies, bibliographical analysis and geographic information systems (GIS). The latter is used to provide a professional map illustrating the spatio-temporal distribution of the multiple awards received by Dion the artist. The findings of the research highlight the highest scale of appreciation an artist can receive. The results of the study also suggest that the outstanding contribution of the greatest artists of the world, acknowledged by the highest national, international and global forums, provide significant information about their artistic involvement in the global popular culture. They have a strong relevance both in space and in time, thus labeling different cultural decades and distinct places and spaces throughout the world.

Monique Leyrac : notre grande dame de la chanson québécoise du XXe siècle - Laberge, Yves (Cap-aux-Diamants : la revue d'histoire du Québec, 2020)
Un article de la revue Cap-aux-Diamants, diffusée par la plateforme Érudit.
Publisher: Les Éditions Cap-aux-Diamants inc.

Céline, es-tu queer ? - Leblanc, Thomas (QuébeQueer. Le queer dans les productions littéraires, artistiques et médiatiques québécoises, 2020)
En plus d’offrir un portrait des productions culturelles queer au Québec tant francophones qu’anglophones, dont certaines autochtones, cet ouvrage s’attarde à révéler le caractère queer de celles qui ne le sont pas de facto. Il se présente comme un manuel de référence sur le sujet, avec des essais critiques – qui portent autant sur la littérature et le monde du spectacle que sur les arts médiatiques ou la presse gay – et des textes expérimentaux – fictions, dessins, récits autobiographiques. Plus de 27 œuvres de fiction publiées entre 1965 et 2017 y sont analysées sous différents aspects, avec des méthodologies diverses, mais toujours sous l’éclairage queer (un terme à la nature instable, paradoxale, que calque la forme éclatée de l’ouvrage). Du polyamour à l’inceste, en passant par le racisme, l’urbanité, le suicide, le non-désir d’enfant, l’alimentation ou les processus de production, le queer met en scène des personnages hétéros ou homosexuels, intersexués, cis, trans, travailleur·euse·s du sexe, gros et plusieurs autres… Cette juxtaposition d’états, de genres, de thèmes, de formes et de pratiques constitue l’une des forces de ce livre qui intéressera bien sûr un lectorat d’intellectuel·le·s et de personnes issues des communautés LGBTQIA2S+, mais pas seulement. Il deviendra, sans nul doute, une ressource indispensable pour l’enseignement de nouvelles perspectives dans le cadre des sciences humaines et sociales.

Venus On Venus: CKUT’s Women’s Collective Music Show Dishes on Feminist Radio - Leventhal, Anna; McInnis, Catherine; Wilson, Angela (Women in Radio: Unfiltered Voices from Canada, 2020)
Three volunteer hosts and programmers of a feminist music show at a campus-community radio station, Anna Leventhal, Catherine McInnis, and Angela Wilson, sat down in 2008 to chat about feminist radio. They discussed the concept of a feminist music show and the possibilities and limitations of female-only spaces; the “fem-con” concept that campus-community radio stations be mandated to play a certain amount of music by women, in the same way they are mandated by the CRTC to play Canadian content; the transformative social and political potential of community radio; and the inclusion of trans and gender-nonconforming voices on the show.

Ageing with Waves: The Im/material Worlds of Two Quebec Ondists - Madden, David (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)
Ageing and memory - two aspects of life everybody has to face eventually. The contributions to this volume explore the cultural mediations of these categories. Through a series of approaches focused on practices and acts of memory, narratives, reminiscence, representation and collective memory, they seek to better understand and critically reflect on how ageing is experienced in variegated ways across the lifespan. By covering a variety of phenomena, from biopics, music by the elderly, and artefacts, among other, they all contribute to further the understanding of memory as a cultural process always in the making - situated in particular contexts, and shaped by its material conditions of existence.

Imaginary Women, Imaginary Audience: Gender and Top 40 Radio in Montréal - Maki, Christine (Women in Radio: Unfiltered Voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audi ence. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit wom en’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.

Tuning a Room: Designs for Hearing According to Nancy Tobin - Rewa, Natalie (Canadian Theatre Review, 2020)
In this review, I discuss the architectonics of sound composition according to sound artist and designer Nancy Tobin. This chapbook advocates for a comprehensively integrated presence of a sound artist in the processes of rehearsal and espouses a dramaturgy of hearing. Tobin’s distinction between hearing and listening gives forth onto a series of self-studies of her experience of spatial and temporal arrangements presented in the form of e-mails to mentees. Her appreciation for the acoustics of the performance space extends to the composition of sound to be heard (on occasion as boldly interventionist) and the technologies of broadcasting it: the choice and placement of speakers, as well as their interaction with the performers. Tobin argues for a definition of sound composition for performance as a complex collaboration with the production—curatorial in terms of the space of ephemerality. My review concurs with the efficacy of her approach by my recognition of the moments in productions that have remained as some of the most memorable of my theatregoing.
Keywords: Nancy Tobin; acoustic space; rehearsal processes; sonic/acoustic dramaturgy; sound artist; speaker specifications and broadcasting sound